2014
DOI: 10.1002/2013ja019085
|View full text |Cite
|
Sign up to set email alerts
|

Magnetosphere‐ionosphere coupling of global Pi2 pulsations

Abstract: Global Pi2 pulsations have mainly been associated with either low/middle latitudes or middle/ high latitudes and, as a result, have been treated as two different types of Pi2 pulsations, either the plasmaspheric cavity resonance or the transient response of the substorm current wedge, respectively. However, in some reports, global Pi2 pulsations have a single period spanning low/middle/high latitudes. This "super" global type has not yet been satisfactorily explained. In particular, it has been a major challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 86 publications
0
18
0
Order By: Relevance
“…It is noted that the low‐latitude H and low‐ to high‐latitude D components of Pi2 pulsations are generated by different physical processes. Kepko et al [], Uozumi et al [, ], and Keiling et al [] suggested that the driving sources of δ B SCW and δ B FW are closely coupled with each other. The present analysis further support their suggestions.…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that the low‐latitude H and low‐ to high‐latitude D components of Pi2 pulsations are generated by different physical processes. Kepko et al [], Uozumi et al [, ], and Keiling et al [] suggested that the driving sources of δ B SCW and δ B FW are closely coupled with each other. The present analysis further support their suggestions.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in section 1, many models have been proposed for Pi2 pulsations during substorm at Earth, including plasmaspheric cavity mode [e.g., Southwood and Kivelson , ; Lin et al ., ], ballooning waves [ Solovyev et al ., ; Keiling , ], bouncing Alfvén waves [e.g., Maltsev et al ., ; Lester et al ., ; Baumjohann and Glaßmeier , ], interchange oscillations in the plasma flow [ Wolf et al ., ; Keiling et al ., ; Panov et al ., ], and the braking of quasi‐periodic flow bursts in the plasma sheet [ Kepko and Kivelson , ; Kepko et al ., ]. Mercury is a very slow rotating planet (i.e., rotation period of ~ 58.6 days).…”
Section: Sources For the Plasma Wavesmentioning
confidence: 99%
“…The Alfvén waves studied here could also be due to mode conversion near the equatorial region [e.g., Keiling et al ., ; Kim et al ., ]. In this model, the compressional waves generated by flow braking in the near equatorial region undergo mode conversion to Alfvén waves, which would propagate along the field line toward the nightside polar region.…”
Section: Sources For the Plasma Wavesmentioning
confidence: 99%
“…This frequency range of DFB‐driven waves was revealed and explored by simultaneous observations of DFBs and magnetic oscillations of such frequencies (e.g., Kepko & Kivelson, ; Shiokawa et al, ). In situ magnetospheric observations showed that the DFB‐driven oscillations cover L shells extending from the GEO to the plasma sheet (e.g., Keiling et al, ; Runov et al, ). At the same time as DFB observations, ground magnetometers recorded Pi2‐band oscillations throughout 40°–70° latitudes, consistent with the spacecraft's wave observations (e.g., Keiling et al, ; Kepko, Kivelson, & Yumoto, ).…”
Section: Introductionmentioning
confidence: 99%